Uji Aktivitas Ekstrak Etanol Biji Buah Merah (Pandanus conoideus Lamk.) terhadap Bakteri Escherichia coli dan Staphylococcus aureus - Asrianto Asrianto; Asrori Asrori; Loly Sabrina Sitompul; Indra Taufik Sahli; Risda Hartati (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Infectious diseases can be caused by one of four different organisms, namely: bacteria, fungi, viruses, and parasites. This study aims to determine the ability and concentration of the best ethanol extract of red fruit seeds (Pandanus conoideus Lamk.) In inhibiting the growth of Escherichia coli and Staphylococcus aureus infectious bacteria. This research is an experimental study using a completely randomized design (CRD). The stages of work carried out consisted of: sample preparation, sample extraction, solution concentration preparation, and inhibition testing. The research work procedure began with the process of preparing a sample of red fruit seeds into powder. The maceration method was used for extraction using 96% ethanol with a ratio of 1: 3. The concentration of the extract was made by mixing the macerated extract with aquadest solvent. The concentration variations made were: 0.31%, 0.63%, 1.25%, and 2.50%. Inhibition testing against bacteria was carried out using the Kirby-Bauer method. The data obtained were analyzed using Analysis of Variance (ANOVA). The results showed that the ethanol extract of red fruit seeds had bioactive compounds that could inhibit the growth of Escherichia coli and Staphylococcus aureus bacteria. The bioactive compounds consist of phenols, flavonoids, steroids, terpenoids, alkaloids, and tannins. The average diameter (mm) of the inhibition zone of Staphylococcus aureus bacteria was greater than the average diameter (mm) of the inhibition zone in Escherichia coli bacteria due to differences in the structure of their cell walls. The increase in the concentration of the solution is directly proportional to the diameter of the formed zone of inhibition. The higher the concentration given, the larger the diameter of the inhibition zone is seen. Duncan test analysis showed that 2.5% ethanol extract concentration was the best concentration in inhibiting bacterial growth.